2003
DOI: 10.1128/jvi.77.4.2741-2746.2003
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Type 2-Mediated Gene Transfer: Role of Cellular T-Cell Protein Tyrosine Phosphatase in Transgene Expression in Established Cell Lines In Vitro and Transgenic Mice In Vivo

Abstract: ). FKBP52 can be phosphorylated at both tyrosine and serine/threonine residues, but only the phosphorylated forms of FKBP52 interact with the D sequence. Furthermore, the tyrosine-phosphorylated FKBP52 inhibits AAV second-strand DNA synthesis by greater than 90%, and the serine/threonine-phosphorylated FKBP52 causes ϳ40% inhibition, whereas the dephosphorylated FKBP52 has no effect on AAV second-strand DNA synthesis. In the present study, we have identified that the tyrosine-phosphorylated form of FKBP52 is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
79
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 47 publications
7
79
0
Order By: Relevance
“…Phosphorylated FKBP52 inhibits the viral second-strand DNA synthesis leading to inefficient transgene expression. [6][7][8][9][10][11] We have also documented that FKBP52 is dephosphorylated at tyrosine residues by the cellular T-cell protein tyrosine phosphatase (TC-PTP), 22,23 which leads to efficient viral …”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Phosphorylated FKBP52 inhibits the viral second-strand DNA synthesis leading to inefficient transgene expression. [6][7][8][9][10][11] We have also documented that FKBP52 is dephosphorylated at tyrosine residues by the cellular T-cell protein tyrosine phosphatase (TC-PTP), 22,23 which leads to efficient viral …”
mentioning
confidence: 99%
“…2,3 Others and we, on the other hand, have suggested that viral second-strand DNA synthesis is the rate-limiting step in AAV-mediated transgene expression. [4][5][6][7][8][9][10][11] We previously observed that following intravenous (i.v.) administration into the tail-vein, AAV vectors selectively target the liver in mice, but less than 5% of hepatocytes express the transgene.…”
mentioning
confidence: 99%
See 3 more Smart Citations